If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -33 + -2 = 7 + -7x Combine like terms: -33 + -2 = -35 -35 = 7 + -7x Solving -35 = 7 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -35 + 7x = 7 + -7x + 7x Combine like terms: -7x + 7x = 0 -35 + 7x = 7 + 0 -35 + 7x = 7 Add '35' to each side of the equation. -35 + 35 + 7x = 7 + 35 Combine like terms: -35 + 35 = 0 0 + 7x = 7 + 35 7x = 7 + 35 Combine like terms: 7 + 35 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| 7x+9-10x=-18 | | 3+2x=75 | | 2x+1y=1.70 | | 1/x+2/x+1 | | 3x-6=-9+25 | | 4r+9+r=-17-8r | | 5x=-10y+30 | | 7-4d=3d-9d+25 | | 0.333(b-9)=b+9 | | 3/4x=9 | | 7=34 | | -1/4x=7 | | 9(c+2)-11=5(2c+3)-2 | | 3/8x=120 | | y-6=4(x-3)+2 | | -7+x=x/10-6 | | x/3.1=6 | | 15y^2=4-7y | | 8+27w=72w | | (x+4/3)(x-7/3) | | 6d+4d+3= | | 8+27w= | | 2x+7=x+25 | | -7+x=34+2x | | 2/7z=6 | | 13t-(5-2t)=5(3t-1) | | 13x+39=65 | | c/4+7+2 | | 3x+-16=-1 | | 252-4x=41x+17 | | 4/3m=12 | | y=-5x^2-11 |